Triaxial and density behaviour of quarry dust based geopolymer cement treated expansive soil with crushed waste glasses for pavement foundation purposes - Onyelowe, Kennedy; Igboayaka, Clifford; Orji, Francis; Ugwuanyi, Henry; Bui Van, Duc (International Journal of Pavement Research and Technology, 2019)
The effect of quarry dust based geopolymer cement (QDbGPC) and crushed waste glasses (CWG) on the triaxial and density characteristics of expansive test soil was investigated under laboratory conditions. Quarry dust is a solid waste the management of which poses a big problem to construction and environmental experts. So also is the management of waste glasses. Then again, the use conventional cement poses everyday threat to the environment as its utilization releases huge amount of CO2 to the environment thereby causing increased global warming. However, the utilization of quarry dust in the synthesis of geopolymer cements which is an eco-friendly geomaterial and by extension its use in the soil treatment protocol is the aim of this work. The test soil was observed to be a poorly graded A-2-6 soil according to USCS and AASHTO classification systems respectively. The treatment exercise showed that the shear characteristics of the treated soil improved consistently. The poisson ratio, porosity and submerged density i mproved with increased additives. The stress-strain relationship improved to a very stiff consistency which satisfies the requirements for subgrade and subbase materials in pavement construction. Finally, the utilization of QDbGPC proved to be a good replacement for conventional cement in terms of environmental issues resulting from CO2 emission, resistant to moisture, heat, sulphate attacks, etc on hydraulically bound materials.
Keywords: Triaxial behaviour; Dry density behaviour; Quarry dust based geopolymer cement; Moisture bound materials; Recycled waste materials